Thioredoxin-interacting protein regulates lipid metabolism via Akt/mTOR pathway in diabetic kidney disease. (October 2016) - Du, Chunyang; Wu, Ming; Liu, Huan; Ren, Yunzhuo; Du, Yunxia; Wu, Haijiang; Wei, Jinying; Liu, Chuxin; Yao, Fang; Wang, Hui; Zhu, Yan; Duan, Huijun; et al.
Abstract: Abnormal lipid metabolism contributes to the renal lipid accumulation, which is associated with diabetic kidney disease, but its precise mechanism remains unclear. The growing evidence demonstrates that thioredoxin-interacting protein is involved in regulating cellular glucose and lipid metabolism. Here, we investigated the effects of thioredoxin-interacting protein on lipid accumulation in diabetic kidney disease. In contrast to the diabetic wild-type mice, the physical and biochemical parameters were improved in the diabetic thioredoxin-interacting protein knockout mice. The increased renal lipid accumulation, expression of acetyl-CoA carboxylase, fatty acid synthase and sterol regulatory element binding protein-1, and phosphorylated Akt and mTOR associated with diabetes in wild-type mice was attenuated in diabetic thioredoxin-interacting protein knockout mice. Furthermore, thioredoxin-interacting protein knockout significantly increased the expression of peroxisome proliferator-activated receptor-α, acyl-coenzyme A oxidase 1 and carnitine palmitoyltransferaser 1 in diabetic kidneys. In vitro experiments, using HK-2 cells, revealed that knockdown of thioredoxin-interacting protein inhibited high glucose-mediated lipid accumulation, expression of acetyl-CoA carboxylase, fatty acid synthase and sterol regulatory element binding protein-1, as well as activation of Akt and mTOR. Moreover, knockdown of thioredoxin-interacting protein reversed high glucose-induced reduction of peroxisome proliferator-activated receptor-α, acyl-coenzyme A oxidase 1 and carnitine palmitoyltransferaser 1 expression in HK-2 cells. Importantly, blockade of Akt/mTOR signaling pathway with LY294002, a specific PI3K inhibitor, replicated these effects of thioredoxin-interacting protein silencing. Taken together, these data suggest that thioredoxin-interacting protein deficiency alleviates diabetic renal lipid accumulation through regulation of Akt/mTOR pathway, thioredoxin-interacting protein may be a potential therapeutic target for diabetic kidney disease.